2017
DOI: 10.1007/s10815-016-0861-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of failing one dose of methotrexate for ectopic pregnancy after in vitro fertilization

Abstract: This is the first study to report that in women with ectopic pregnancies after IVF, higher hCG-though well below treatment failure thresholds previously described in spontaneous pregnancies-fewer embryos transferred, and adnexal masses are associated with greater odds of failing one dose of MTX. These findings can be used to counsel IVF patients regarding the likelihood of success with single-dose MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…These findings were compatible with the current literature. 26,27 Three cervical and four cesarean scar EPs were successfully treated with medical therapy and no further surgical interventions were needed in our study. This is an important point because cervical and cesarean scar EPs are complicated cases that can cause abundant bleeding, with life-threatening conditions that require surgery in most situations.…”
Section: Discussionmentioning
confidence: 87%
“…These findings were compatible with the current literature. 26,27 Three cervical and four cesarean scar EPs were successfully treated with medical therapy and no further surgical interventions were needed in our study. This is an important point because cervical and cesarean scar EPs are complicated cases that can cause abundant bleeding, with life-threatening conditions that require surgery in most situations.…”
Section: Discussionmentioning
confidence: 87%
“…We feel this case demonstrates failure of MTX in ectopic pregnancy after infertility treatment with IVF. Patients who undergo assisted reproductive technology, specifically IVF, are at an increased risk of developing an ectopic pregnancy with risk at approximately 1.7% [1,2]. Additional risk factors of ectopic pregnancy are fresh embryo transfer, pelvic inflammatory disease, previous appendectomy, tubal pathology, pelvic surgery, and uterine cavity abnormailities [2].…”
Section: Discussionmentioning
confidence: 99%
“…Additional risk factors of ectopic pregnancy are fresh embryo transfer, pelvic inflammatory disease, previous appendectomy, tubal pathology, pelvic surgery, and uterine cavity abnormailities [2]. Specifically in the case of IVF population of patients, there is a higher incidence of tubal disease as the underlying cause of the infertility, suggesting an increased risk of tubal pathology in this population [1]. Research has also suggested that altered physiology due to synthetic cycling and retrograde movement of the embryos during IVF create an increased risk for ectopic pregnancy [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations